Tnfa andIl-10 deficiencies have contrasting effects on lung tumor susceptibility: Gender-dependent modulation of IL-10 haploin sufficiency - Bernert, Heike; Sekikawa, Kenji; Radcliffe, Richard A.; Iraqi, Fuad; You, Ming; Malkinson, Alvin M. (Wiley, 2003)
Epidemiologic evidence suggests that pulmonary diseases with a prominent chronic inflammatory component elevate lung cancer risk. Genetic manipulations of mouse models of lung inflammation and tumorigenesis can be used to investigate this association. The genes encoding pro‐inflammatory tumor necrosis factor‐α (TNFα) and antiinflammatory IL‐10 cytokines map within quantitative trait loci that regulate susceptibility to lung tumor development in mice; sensitive A/J and resistant C57BL/6J (B6) mice have different Tnfa and Il‐10 alleles. Genetic ablation studies were performed to examine whether these genes would qualify as candidate tumor modifiers. Tnfa null (−/−) mice on a B6 background and B6.129 Il‐10−/− mice were intercrossed with A/J mice and subjected to urethane carcinogenesis; lung tumor multiplicity was determined 20 weeks later. In the absence of one copy of Tnfa, tumor number. Male Il‐10+/+ mice developed more tumors than did female mice (P < 0.001), absence of one copy of Il‐10 raised tumor number in female mice to that observed in +/+ males, but no change in multiplicity occurred in Il‐10 hemizygous males. Thus, a deficit of pro‐inflammatory TNFα decreased the number of tumors, whereas diminished gene copy number of anti‐inflammatory IL‐10 increased tumorigenesis; manifestation of an effect of Il‐10 haploinsufficiency is gender dependent. These studies support a role for inflammation in lung cancer susceptibility. © 2003 Wiley‐Liss, Inc.